Against (the use of the term) ‘spiritual education’ - Marples, Roger (International journal of children's spirituality, 2006)
The paper argues that the term ‘spiritual education’ is completely otiose. It tries to show that its application in both religious and secular contexts is deeply problematic. If there is any such form of knowledge or understanding, it is difficult to see how children are to be initiated into it without being indoctrinated. The paper focuses on a number of recent philosophical attempts to defend the use of the term within religious and non‐religious contexts, and attempts to highlight the respects in which these cannot possibly succeed unless and until the concept is shown to possess features by reference to which we might distinguish it from other forms of knowledge and understanding with a rightful place on the curriculum. Until it can be demonstrated that there is any such thing as spiritual knowledge, with its own subject matter and conceptual apparatus, providing some sort of basis on which spiritual education might proceed, we have reason to be sceptical about the coherence of the whole enterprise of attending to children’s spiritual education and their so‐called spiritual development.